DETERMINASI PENGANGGURAN USIA MUDA DI PROVINSI ACEH, STUDI KASUS: TIGA KABUPATEN/KOTA - Nasriati, Nasriati (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2023)
Youth unemployment is a persistent problem in several regions of Indonesia, including Aceh Province. This study aims to analyze the determinants of youth unemployment by focusing on three selected areas: Aceh Barat, Lhokseumawe, and Banda Aceh, using panel data from 2019 to 2024. A quantitative approach was employed, with education and inflation as the independent variables and youth unemployment as the dependent variable. Panel regression was conducted using the Fixed Effect Model (FEM), which was selected through Chow and Hausman tests. The findings reveal that education has a negative and statistically significant effect on youth unemployment, suggesting that an increase in education levels reduces unemployment among young people. Conversely, inflation has a positive and significant impact, indicating that rising prices contribute to higher unemployment rates among youth. These results highlight the importance of human capital development through improved access to education and the need for macroeconomic stability, particularly in controlling inflation, to reduce youth unemployment in the region.